2017
DOI: 10.32677/ijch.2017.v04.i03.038
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of congenital diaphragmatic hernia and their short-term outcome in a tertiary care neonatal unit: A retrospective study

Abstract: ongenital diaphragmatic hernia (CDH) remains one of the most difficult problems of the perinatology and neonatal surgery. Western literature showing 90% of survival rate is not reflected in our population. Initial stabilization of the neonate with advanced ventilatory techniques and optimal management of associated pulmonary hypertension by the neonatologist has significantly lowered the operative mortality in developed countries. However, the mortality rate in developing countries is still 40-50% [1]. Several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Studies from other Indian centers have reported survival rate ranging from 58% to 78%. [234] On the other hand, studies from developed countries have reported a survival rate of 85%–90% with protocolized care. [67]…”
Section: Discussionmentioning
confidence: 99%
“…Studies from other Indian centers have reported survival rate ranging from 58% to 78%. [234] On the other hand, studies from developed countries have reported a survival rate of 85%–90% with protocolized care. [67]…”
Section: Discussionmentioning
confidence: 99%
“…Over the past two decades, studies from South and Southeast (SE) Asian countries, mostly involving relatively small numbers of neonates and with varying selection criteria, report survival rates ranging from 56-78% in India [14][15][16][17][18], 52% in Malaysia [19], and 56-79% in Taiwan [20,21] and Singapore [8,22], moving from low-middle, upper-middle, and high-income countries, respectively. Antenatal diagnosis varies between 5-79% in these studies and risk factors for non-survival include an antenatal diagnosis, low Apgar score, the presence of moderate-to-severe persistent pulmonary hypertension of the newborn (PPHN), pneumothorax, and high oxygenation index (OI).…”
Section: Introductionmentioning
confidence: 99%